Charge engineering reveals the roles of ionizable side chains in electrospray ionization mass spectrometry - Abramsson, ML; Sahin, C; Hopper, JTS; Branca, RMM; Danielsson, J; Xu, M; Chandler, SA; Österlund, N; Ilag, LL; Leppert, A; Costeira-Paulo, J; Lang, L; et al. (American Chemical Society, 2021)
In solution, the charge of a protein is intricately linked to its stability, but electrospray ionization distorts this connection, potentially limiting the ability of native mass spectrometry to inform about protein structure and dynamics. How the behavior of intact proteins in the gas phase depends on the presence and distribution of ionizable surface residues has been difficult to answer because multiple chargeable sites are present in virtually all proteins. Turning to protein engineering, we show that ionizable side chains are completely dispensable for charging under native conditions, but if present, they are preferential protonation sites. The absence of ionizable side chains results in identical charge state distributions under native-like and denaturing conditions, while coexisting conformers can be distinguished using ion mobility separation. An excess of ionizable side chains, on the other hand, effectively modulates protein ion stability. In fact, moving a single ionizable group can dramatically alter the gas-phase conformation of a protein ion. We conclude that although the sum of the charges is governed solely by Coulombic terms, their locations affect the stability of the protein in the gas phase.